2018
DOI: 10.1039/c8ta00070k
|View full text |Cite
|
Sign up to set email alerts
|

Probing the active sites of Co3O4 for the acidic oxygen evolution reaction by modulating the Co2+/Co3+ ratio

Abstract: Synthesis of Ag doped Co3O4 with different atomic ratios of Co2+/Co3+ and investigation of the effect of preferential exposure of Co2+ in Co3O4 on the acidic OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(80 citation statements)
references
References 54 publications
5
72
1
Order By: Relevance
“…[8] As imilars trong band at 198 cm À1 is observed in Table S2 in the Supporting Information). Upon increasing the temperature, the Zn/Co ratio gradually decreases, which indicates ah igh degree of volatilization of nanosizedZ na th igher temperature;t his is also consistent with TXRF results ( Table S1 in [8,52] The O A /O L ratio increases with the introduction of Zn, the linear sweep voltammetry (LSV) curves, for which 50 mA cm À2 was chosen as an indicator due to the rapid rising current for the oxidation of Co 3 + to Co 4 + at about 1.5 V. [21] /NC-CNT-X could play more criticalr oles in activation of the catalytic sites by decreasingt he adsorption energy of H 2 Om olecules onto the active sites, andt hus, leading to an increasei nt he OER activity. [54,56] DFT calculations have suggestedt hat the existence of oxygen vacancies could decrease the hindrance of the adsorption of H 2 O/OH À at low-coordination Co 3 + sites.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…[8] As imilars trong band at 198 cm À1 is observed in Table S2 in the Supporting Information). Upon increasing the temperature, the Zn/Co ratio gradually decreases, which indicates ah igh degree of volatilization of nanosizedZ na th igher temperature;t his is also consistent with TXRF results ( Table S1 in [8,52] The O A /O L ratio increases with the introduction of Zn, the linear sweep voltammetry (LSV) curves, for which 50 mA cm À2 was chosen as an indicator due to the rapid rising current for the oxidation of Co 3 + to Co 4 + at about 1.5 V. [21] /NC-CNT-X could play more criticalr oles in activation of the catalytic sites by decreasingt he adsorption energy of H 2 Om olecules onto the active sites, andt hus, leading to an increasei nt he OER activity. [54,56] DFT calculations have suggestedt hat the existence of oxygen vacancies could decrease the hindrance of the adsorption of H 2 O/OH À at low-coordination Co 3 + sites.…”
Section: Resultssupporting
confidence: 86%
“…The HR N 1 s XPS results can be deconvoluted into three peaks located at 398.7, 399.8, and 401.6 eV (Figure S6 D in the Supporting Information), which can be assigned to pyridinic N, pyrrolic N, and quaternary N, respectively. The O 1 s spectrum (Figure S6 E in the Supporting Information) displays two oxygen states at around 529.9 and 531.5 eV, which are related to lattice oxygen bound to metals (O L ) and oxygen vacancies on the surface (O A ) . The O A /O L ratio increases with the introduction of Zn, which indicates a higher concentration of vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…[31,32] With aview to sustainability and cost, silver has ar obust electrochemical stability in alkaline conditions and ar elatively reasonable price compared to rare-earth elements,i ncluding noble metals.T herefore,e ngineering Co 3 O 4 structure via coupling with conductive Ag particles could be employed as an effective strategy to improve its electrocatalytic performance. [32][33][34][35][36] Obviously,t he formation of metallic Ag is beneficial for the electrical conductivity of Co 3 O 4 . [35][36][37][38] Moreover, recently Zeng et al observed that less than 1% of Ag + cations addition to CoSe 2 could facilitate the charge transfer process that serves as the key step in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[51,52] The electrochemical impedance spectroscopy (EIS) was employed to further investigate the OER kinetics. [53] We next investigated the effect of electrochemically active surface area (ECSA) toward OER performance. The fitting results suggest that UfD-RuO 2 / CC has a much smaller charge transfer resistance (1.4 Ω) than RuO 2 /CC (41.4 Ω), confirming the higher charge transfer rate and faster OER kinetics of UfD-RuO 2 /CC.…”
mentioning
confidence: 99%